Virtual goods and value perception - Huikko, Iiro (2012)
Huikko, Iiro Virtual goods and value perception Jyväskylä: University of Jyväskylä, 2011, 28 p. Information Systems, Bachelor’s Thesis Supervisor: Seppänen, Ville During the last decade the market of virtual goods has grown from the petty exchange of virtual artifacts into a booming multi-billion dollar business. Data shows that in 2007 global revenue of virtual goods was $2.1 billion when in 2010 it had raised to $7.3 billion. That is an increase of over 240 percent. To give some perspective in 2010 the global box office revenue of movies was $31.8 billion. That means the revenue of virtual goods was over a fifth of box office revenue. Some analysts predict that come 2014 the revenue has climbed up to $14 billion. This raises many questions and points out that people place real value on virtual goods. Games like Second Life, Habbo hotel and Farmville have shown that virtual goods are not just for “nerds” anymore, but for everyone. The target of this thesis is to tell what virtual goods are, where and how virtual business takes place and how people perceive value of virtual goods. This is done by combining research on virtual goods and theory of value. The results show that in most ways the value of virtual goods complies with the theory used in this thesis but there are some fundamental differences.